2023
DOI: 10.1177/17588359231169981
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of the combination of TP and PF regimens with or without immune checkpoint inhibitors for the first-line treatment of locally advanced or advanced esophageal squamous cell carcinoma

Abstract: Objective: To investigate the efficacy and safety differences between the cisplatin + paclitaxel (TP) and cisplatin + fluorouracil (PF) regimens in combination with or without immune checkpoint inhibitors (ICIs) in advanced esophageal squamous cell carcinoma (ESCC) first-line treatment and prognostic factors. Methods: We selected the medical records of patients with late stage ESCC admitted to the hospital between 2019 and 2021. Based on the first-line treatment regimen, control groups were divided into chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The salient features of the incorporated articles are succinctly outlined in Table 2 . Three of these investigations were conducted in Japan 23 , 28 , 29 , and five in China 24 , 26 , 27 , 30 , 31 . The range of NOS scores observed in the research encompassed values between 6 and 9, signifying that all included studies exhibited a high level of quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The salient features of the incorporated articles are succinctly outlined in Table 2 . Three of these investigations were conducted in Japan 23 , 28 , 29 , and five in China 24 , 26 , 27 , 30 , 31 . The range of NOS scores observed in the research encompassed values between 6 and 9, signifying that all included studies exhibited a high level of quality.…”
Section: Resultsmentioning
confidence: 99%
“…All seven studies included in the analysis were retrospective 23 , 24 , 26 , 28 31 , while one was single-arm study 27 . Two studies were conducted in patients diagnosed with ESCC patients 30 , 31 ; one study was in HCC patients 27 , one study was in esophageal cancer (EC) patients 26 , one study was in GC patients 24 , one study was in NSCLC patients 23 , one study was in squamous cell carcinoma of the head and neck (HNSCC) patients 28 , and one study was in RCC patients 29 . Furthermore, 7 studies reported CONUT’s role in prognosticating OS outcome 23 , 24 , 26 , 28 31 , all 8 studies provided the data of CONUT for PFS prognosis 23 , 24 , 26 31 , 3 studies provided the data of CONUT for DCR prognosis 23 , 26 , 28 , and 4 studies provided the data of CONUT for ORR prognosis 23 , 26 , 28 , 31 .…”
Section: Resultsmentioning
confidence: 99%
“…The chemotherapy regimens used in clinical practice in different regions are also not unified. In China, the TP regimen is mainly used, while in other countries, the PF regimen is more popular ( 16 ). The results of this study showed that the median PFS of patients with PD-1 inhibitors combined with the TP regimen was more than one month longer than that of patients with the combined PF regimen, and there was statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study on the first-line treatment of locally advanced or advanced ESCC with or without TP and PF combined with immune checkpoint inhibitors (ICIs), it was found that the ORR and DCR in the TP+ICIs group were 42.1% (50/119) and 97.5% (116/119), respectively, which were 6.6% and 7.2% higher than those in the PF+ICIs group. Regardless of whether the TP regimen is combined with ICI or not, the PFS and OS benefits of the TP regimen are significantly better than those of the PF regimen ( 16 ). Related studies have shown that in clinical trials, the ORR of patients receiving PD-1 inhibitors combined with TP or FP seems to vary, possibly due to different chemotherapy regimens that may cause different changes in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Currently, the combination of chemotherapy and ICIs has become the standard first-line treatment for patients with ESCC and is widely used during clinical practices. 7 A series of Phase III clinical trials, such as KEYNOTE-590, 8 CheckMate 648, 9 ESCORT-1ST, 10 JUPITER-06, 11 ORIENT-15, 12 ASTRUM-007 13 and RATIONALE 306, 14 have demonstrated that the combination of anti-PD-1 antibody significantly improved progression-free survival (PFS) and overall survival (OS) as compared with chemotherapy alone in patients with advanced or metastatic ESCC. 15 Furthermore, several studies have indicated that platinum in combination with taxol (TP) + ICIs may offer advantages over platinum in combination with fluorouracil (PF) + ICIs for advanced or metastatic ESCC.…”
Section: Introductionmentioning
confidence: 99%